Banten Pasca Agresi Militer Belanda Kedua - Suharto, Suharto (Makara Human Behavior Studies in Asia, 2009)
The aim of this researh is to expose the phenomenon in Banten Residency after the Dutch occupied the region. There are four steps used in this research, i.e. collecting historical sources (heuristic), critique, interpretation and historiography (writing the history). This research result that the two sides of the civil government did not work well. Not long after Banten was occupied by the Dutch, several prominent Bantenese figures, especially those who were proDutch discussed the future status of the region. The Information Department of Banten Residency who was pro-Dutch offered several alternatives for the people of Banten to choose. The alternatives were: (1) Banten became the 13th province of the Dutch Kingdom; (2) Banten joined the United States of Indonesia as a state or got a special status; (3) Banten indirectly joined the United States of Indonesia. First this region joined the state of Pasundan or the Federal District of Jakarta. If Banten joined the state of Pasundan, there are two options, firstly this district as a residency or secondly, as a state or an exclusive territory. Those alternatives were presented to the People Representative Board of Banten for the people to choose and to appoint a delegation who would present their choice to the Round Table Conference in the Hague (Den Haag). But the body did not follow the aspiration of the representative board. This body just had to wait for the conference decision. Based on the conference decision, Banten remained as a part of the Republic of Indonesia which was a state in the United States of Indonesia.